PERLINDUNGAN HUKUM TERHADAP ISTRI DAN ANAK HASIL POLIGAMI SIRRI DI LOMBOK - Muhlas Muhlas (Jurnal Pembaharuan Hukum, 2017)
Fanaticism on the teachings of Islam in Lombok is very strong, many unregistered marriagesand divorce outside their congregation believes that it is legitimate according to religion and themajority of Lombok people’s belief, but it does not affect the low protection of wives and childrenof polygamy sirri. In this paper the author tries to explore the weaknesses of legal protectionof wives and children resulting from polygamy sirri in Lombok today By using the approachof social legal risecht, which is used in research based on the paradigm of constructivism theauthor seeks to find legal issues faced by the wife and child results Polygamy sirri in Lombok.The result is polygamy sirri which is continuously done by people who only rely on fikh doctrinewithout regard to other legal doctrine (Positive law) it will cause discrimination to woman (wife)and child because do not have base of protection.